Levels of self-compassion and coping with daily demands in Elementary Education students (European Journal of Child Development, Education and Psychopathology, 2023)
Inevitably, in their day-to-day Elementary Education students must face multiple and heterogeneous academic and extra-academic demands. These daily demands constitute a potential threat to child well-being. Therefore, the identification of personal resources that favor more constructive ways of coping acquires special importance. From this proactive approach, the present study analyzed the role of self-compassion in coping with daily demands in Elementary Education students. Specifically, the study examined the differences between the coping strategies of the students based on their level of self-compassion. The sample was composed by 487 students from fourth, fifth and sixth years of Elementary Education. An ex post facto cross-sectional design was carried out. The students with higher levels of self-compassion showed a significantly higher use of all the approach-coping strategies evaluated. On the contrary, the use of unproductive coping strategies was significantly lower in the more self-compassionate students. These findings suggest that self-compassion can be an effective personal resource when it comes to favoring adaptive coping with daily demands in the upper years of Elementary Education.
Keywords: self-compassion; everyday demands; coping; students; Elementary Education